PENGARUH MEDIA 3D ANOTRUS TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA - Marettha Ania; Berti Yolida; Rini Rita Marpaung (Universitas Lampung, 2016)
This research aim was to understand the influence of 3D media anotrus toward improvement of students activities and learning outcomes. The research was conducted on SMPN 3 Tanjung Raja. Samples were students of VIIIA and VIIIB calss which were selected by purposive sampling technique. The research design was non-equivalent pre-test and post-test. Qualitative data were learning outcomes that were obtained from pretest and posttest that analyzed with u-test and t-test. Qualitative data were students activities of observation and students responses on 3D media anotrus that were obtained from descriptive analyzed of questionnaires. Results of the research showed that learning outcomes in experiment class was significantly different from data control class. The average percentage of students activities on experiment class showed higher improvement. Students also gave positive response to 3D media anotrus. Thus, 3D media anotrus influence significantly to improved students activities and learning outcomes.Penelitian ini bertujuan untuk mengetahui pengaruh media 3D Anotrus terhadap peningkatan aktivitas dan hasil belajar siswa. Penelitian yang dilakukan di SMPN 3 Tanjung Raja. Sampel adalah siswa kelas VIIIA dan VIIIB yang dipilih dengan teknik Purposive sampling. Desain penelitian menggunakan pretes postes tak equivalen. Data penelitian berupa Data kuantitatif yaitu hasil belajar siswa yang diperoleh dari pretes dan postes yang dianalisis menggunakan uji u dan uji-t, Data kualitatif yaitu data aktivitas siswa yang diperoleh dari observasi dan tanggapan terhadap media 3D Anotrus diperoleh dari angket yang dianalisis secara deskriptif. Hasil penelitian menunjukkan hasil belajar kelas eksperimen berbeda signifikan dengan kelas kontrol. Rata-rata persentase aktivitas siswa kelas eksperimen menunjukkan peningkatan yang lebih tinggi. Siswa memberikan tanggapan positif terhadap media 3D Anotrus. Dengan demikian, penggunaan media 3D Anotrus berpengaruh terhadap peningkatan aktivitas siswa dan hasil belajar siswa.Kata kunci : aktivitas, hasil belajar siswa, media 3D Anotrus